(untitled) (Rome, Italy, 2003)
This publication is meant to assist countries in developing links between sustainable forest management and other sectors and in developing effective national policy frameworks and national forest programmes; and will contribute to enhanced coordination in policy formulation and implementation, thus minimizing negative impacts on forests and promoting sustainable forest management and people's well-being.
Keywords: Forests and forestry